Evaluation of evidence of prevention and management of facial pressure injuries in medical staff. Issue 5 (11th December 2022) - Su, Honghong; Lv, Qian; Kong, Yue; Zeng, Huiling; Zhou, Wenguang; Zhu, Fangfang; Xu, Baoling; Zhou, Qijun
Abstract: Aim: This systematic review evaluated the quality of evidence for the prevention and management of facial pressure injuries in medical staff. Design: This review was presented in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Methods: We retrieved the relevant studies from 19 databases. Using the literature evaluation standards and evidence grading system of the Australian Joanna Briggs Institute Evidence‐Based Health Care Center, we evaluated the quality of the literature encompassing different types of research and assessed their levels of evidence. Results: A total of 13 studies were included, including seven expert consensuses, two recommended practices, one clinical decision, one best practice information booklet, one systematic review and one randomized controlled trial. In the end, 31 best evidence were summarized, including skin cleaning and care, PPE placement and movement, reasonable use of dressings, treatment measures and education and training.